A Review of the Control Networks, Communication Protocols, and Algorithms of Building Automation System - Thangatamilan.M, Suji Prasad.S.J, Sagana.C, Suganesh.R (International Journal of Control and Automation, 2020)
The increasing global environmental issues with the rapid increase in energy utilization constitute a significant concern. The new terms, such as the energy-intelligent buildings are emerging, and energy efficiency is the critical factor in the constructions.  The Building automation system (BAS) is used to improve the energy performance of the building. In large buildings, the operation costs are much reduced due to the installation of the building automation systems. The building automation system will integrate the different building services and controls them. The main problem for developing the building automation system is the interoperability of the devices from different manufacturers. The solution to the interoperability is using open protocols such as BACnet, LonWorks, and KNX. In this paper presents a detailed report on the design, operation, control, and the comparison of the communication protocols of the building automation system. ​